Essays. Lydia Davis. - Davis, Lydia (Londen : Penguin, Random House, 2019)
Mitchell, Joan ; Cornell, Joseph ; Cote, Alan ; Leiris, Michel
verzamelde kunstkritieken literatuur en beeldende kunst
boek
Keywords: Lydia Davis